2020
DOI: 10.1016/j.jaim.2020.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Single garlic oil modulates T cells activation and proinflammatory cytokine in mice with high fat diet

Abstract: Background Hyperlipidemia triggers atherosclerosis by involving immune cells, such as T-cells. T-cells plays a role in worsening conditions during a high-fat diet (HFD). Objective The research aimed to analyze the role of single garlic oil (SGO) on T-cells activation and its proinflammatory cytokine expression in HFD mice. Methods Mice were divided into six groups: ND (normal diet); HFD (high-fat diet without treatment); HFD + Simv (HFD + sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…DCs commonly expressed CD11c and MHC class II, and the expression was increased once DCs is activated to activate naïve T cells [ 9 ]. Interestingly, memory CD4 + T cells mainly migrated to inflammatory sites, driving obesity−associated insulin resistance together with CD8 + in adipose tissue [ 53 , 54 ]. In line with our result, HFD resulting in the lower expression of CD4 + CD62L + , thus interrupt the lymphocyte and erythrocyte homeostasis [ 53 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…DCs commonly expressed CD11c and MHC class II, and the expression was increased once DCs is activated to activate naïve T cells [ 9 ]. Interestingly, memory CD4 + T cells mainly migrated to inflammatory sites, driving obesity−associated insulin resistance together with CD8 + in adipose tissue [ 53 , 54 ]. In line with our result, HFD resulting in the lower expression of CD4 + CD62L + , thus interrupt the lymphocyte and erythrocyte homeostasis [ 53 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study confirmed that Single garlic oil could suppress CD4 t-cells activation and NF-κB Frontiers in Pharmacology frontiersin.org expression in high-fat diet mice. Furthermore, Single garlic oil plays a role as an athero-protective agent in the High-fat diet condition through the decrease in proinflammatory cytokines such as TNF-a and IFN-g (Lestari et al, 2020). SGO could act as a promising prospect for therapy to improve chronic inflammation in AS.…”
Section: Anti-inflammatorymentioning
confidence: 99%
“…During bacterial infection, macrophages expressed Toll-like receptors 4 (TLR4), which primarily recognizes the lipopolysaccharide (LPS) as the major component of the cell wall of S. typhi . This recognition subsequently stimulates TLR4 signaling pathways, such as NFκB, to produce proinflammatory cytokines, resulting in increased systemic cytokine production and septic shock in the later stages [ [8] , [9] , [10] ].…”
Section: Introductionmentioning
confidence: 99%